POLITIK ANGGARAN PROVINSI JAWA TENGAH : ANALISIS REALISASI APBD PROVINSI JAWA TENGAH TAHUN ANGGARAN 2008-2010 - Agus Riyanto (SPEKTRUM, 2012)
Abstract The local Budget  revenue and expenditure or APBD  is annual financial plan  that made by  local government with local parliament (DPRD), which is describes activate and program plan to achieve the local medium development  plan (RPJMD). The or APBD should be optimized to achieve the public welfare which is the purpose of the local government.  This article will analyze the realization of the local budget of central java in 2008 until 2010.  The research problem is “how  the budget realization in the Local revenue and expenditure budget (APBD) of the Province of Central Java in 2008 until 2010? Key words : Local budget or APBD, apparatus expenditure, public expenditure, Local Medium Development Plan (RPJMD), Vision and Mission.